1987
DOI: 10.1164/ajrccm/136.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function in Prematurely Delivered Rabbits Treated with a Synthetic Surfactant

Abstract: We treated prematurely delivered rabbit pups with the synthetic surfactant that has been named Exosurf. By weight, Exosurf is 61.8% dipalmitoylphosphatidylcholine, 6.8% hexadecanol, 4.6% tyloxapol, and 26.7% NaCl. This simple mixture, suspended at 15 mg lipid X ml-1 water, has appropriate in vitro characteristics for a lung surfactant substitute. As determined by static pressure volume relationships performed after 30 min ventilation, lungs treated with Exosurf accepted significantly more gas at maximal inflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 7 publications
3
23
0
Order By: Relevance
“…In animal studies, several investigators have shown an improvement in Cdyn after surfactant treatment in immature lung disease (4)(5)(6)(7)(8). In our study, there were also differences in Cdyn between surfactanttreated and untreated animals, with significantly higher Cdyn in the treated group.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In animal studies, several investigators have shown an improvement in Cdyn after surfactant treatment in immature lung disease (4)(5)(6)(7)(8). In our study, there were also differences in Cdyn between surfactanttreated and untreated animals, with significantly higher Cdyn in the treated group.…”
Section: Resultssupporting
confidence: 71%
“…The techniques used in this study should also be useful to evaluate lung function in preterm human infants after specific adaptation of the equipment size. (1)(2)(3)(4)(5)(6)(7)(8), clinical course, and outcome (9-1 1). It has also been suggested that prophylactic surfactant treatment before initiation of spontaneous or mechanical ventilation is the best way to prevent injury to distal conducting airways, i.e.…”
Section: Depur/men/ Ofpediutrics Vanderbilt University School Of Medmentioning
confidence: 99%
“…These differences in response between BS and SS may reflect differences in physicochemical properties between the two surfactant preparations. When used to treat newborn premature rabbit pups before air breathing, SS had a less intense beneficial effect on lung mechanical properties than natural surface-active material ( 16). This difference was attributed to the absence of surfactant apoproteins in SS and to properties such as adsorption rate and spreading.…”
Section: Discussionmentioning
confidence: 99%
“…This liquid plug instillation approach has been an effective delivery method for surfactant replacement therapy, in which microliters of pharmaceutical pulmonary surfactant are instilled into the lungs to treat respiratory distress syndrome (13)(14)(15)(16). Although the plug instillation approach is rather invasive and more suitable for treatment in the inpatient setting, improved therapeutic effect could be achieved with minimal systemic absorption and more precise determination of the effective drug dose (12).…”
mentioning
confidence: 99%